Roles of taurine-mediated tonic GABAA receptor activation in the radial migration of neurons in the fetal mouse cerebral cortex - Furukawa, Tomonori; Yamada, Junko; Akita, Tenpei; Matsushima, Yoshitaka; Yanagawa, Yuchio; Fukuda, Atsuo (Frontiers in Cellular Neuroscience, 2014)
γ-Aminobutyric acid (GABA) depolarizes embryonic cerebrocortical neurons and continuous activation of the GABAA receptor (GABAAR) contributes to their tonic depolarization. Although multiple reports have demonstrated a role of GABAAR activation in neocortical development, including in migration, most of these studies have used pharmacological blockers. Herein, we performed in utero electroporation in GABA synthesis-lacking homozygous GAD67-GFP knock-in mice (GAD67GFP/GFP) to label neurons born in the ventricular zone. Three days after electroporation, there were no differences in the distribution of labeled cells between the genotypes. The dose-response properties of cells labeled to detect GABA were equivalent among genotypes. However, continuous blockade of GABAAR with the GABAAR antagonist SR95531 accelerated radial migration. This effect of GABAAR blockade in GAD67GFP/GFP mice suggested a role for alternative endogenous GABAAR agonists. Thus, we tested the role of taurine, which is derived from maternal blood but is abundant in the fetal brain. The taurine-evoked currents in labeled cells were mediated by GABAAR. Taurine uptake was blocked by a taurine transporter inhibitor, 2-(guanidino)ethanesulfonic acid (GES), and taurine release was blocked by a volume-sensitive anion channel blocker, 4-(2-butyl-6,7-dichlor-2-cyclopentylindan-1-on-5-yl) oxobutyric acid (DCPIB), as examined through high-performance liquid chromatography (HPLC). GES increased the extracellular taurine concentration and induced an inward shift of the holding current, which was reversed by SR95531. In a taurine-deficient mouse model, the GABAAR-mediated tonic currents were greatly reduced, and radial migration was accelerated. As the tonic currents were equivalent among the genotypes of GAD67-GFP knock-in mice, taurine, rather than GABA, might play a major role as an endogenous agonist of embryonic tonic GABAAR conductance, regulating the radial migration of neurons in the developing neocortex.